ANALISA KINERJA RUAS JALAN WAHID HASYIM II DI SAMARINDA - AZIS, HERMANTON M SAID (KURVA S JURNAL MAHASISWA, 2017)
Wahid Hasyim II Roads in Samarinda is a collector street that serve the transportation function of collecting or divider with characteristic medium distance trips, the average speed was, and the number of driveways is limited. Wahid Hasyim II Roads in Samarinda, including category III class road C. As the development of the economy and rising levels of affluence of the population will result in increasing levels of traffic trips, which occur due to the need for transportation of people, where people will always find a way that is faster, safely and smoothly. The increase in population and urbanization many urban areas it will cause a degree of movement and density, so the need for transportation has increased as well. On this basis,As for the Performance Analysis of Wahid Hasyim II Roads uses the Indonesian Highway Capacity Manual (MKJI'1997), which is described by Form UR-1 in the form of general conditions and Geometric road, UR-2 in the form of input data that flows and composition advanced traffic and obstacles aside, UR-3 in the form of analysis is the free flow of light vehicles Speed, Capacity and Speed of light vehicles.In studies Performance Analysis Wahid Hasyim II Roads this survey peak hours for 2 weeks, the first week and the second week Bengkuring intersection at Simpang Ring Road and the survey was conducted in the hours 07:00 to 9:00,12:00 to 14:00, 16:00 to 18:00 and 20.00- 22:00. After calculation of existing data, the intersection Bengkuring segment 1 hour peak occurred on Monday, on traffic volume amounted to 1607.20 smp / hour, degree of saturation of 0.46, Speed 34 km / h, takes 0.0491 hours and service levels are at a C level, which means a stable flow zone, the driver choose the speed limit. Then at the intersection of Ring Road segment 2 hour peak occurred on Saturday, in the traffic volume amounted to 1349.50 smp / hour, degree of saturation of 0.44, Speed 34 km / take 0,0491 hours and service level are at a B level, which means a stable flow zone, the driver has the freedom to choose the speed.